1999
DOI: 10.1073/pnas.96.10.5808
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin-6: An intracellular vesicle water channel protein in renal epithelia

Abstract: All characterized mammalian aquaporins (AQPs) are localized to plasma membranes where they function chief ly to mediate water transport across cells. Here we show that AQP6 is localized exclusively in intracellular membranes in renal epithelia. By using a polyclonal antibody to the C terminus of AQP6, immunoblots revealed a major 30-kDa band in membranes from rat renal cortex and medulla. Endoglycosidase treatment demonstrated presence of an intracellular high mannose glycan on each subunit. Sequential ultrace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
176
0
4

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 239 publications
(194 citation statements)
references
References 29 publications
13
176
0
4
Order By: Relevance
“…This channel colocalizes with the H ϩ -ATPase in intracellular vesicles in the renal collecting duct (73). In the present study, the only AQP that is impermeable to H 2 O is rAQP6.…”
Section: Functional Analysis Of Aqp0 -9mentioning
confidence: 75%
“…This channel colocalizes with the H ϩ -ATPase in intracellular vesicles in the renal collecting duct (73). In the present study, the only AQP that is impermeable to H 2 O is rAQP6.…”
Section: Functional Analysis Of Aqp0 -9mentioning
confidence: 75%
“…For immunoelectron microscopy, the frozen samples were freeze-substituted in a Reichert AFS freeze substitution unit (20,25,27,33). In brief, the samples were sequentially equilibrated over 3 days in methanol containing 0.5% uranyl acetate at temperatures gradually raised from Ϫ80 to Ϫ70°C and, then rinsed in pure methanol for 24 h while the temperature was increased from Ϫ70 to Ϫ45°C.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, the high surface-to-volume ratio of endosomes and other organelles, generally Ͼ3 ϫ 10 5 cm Ϫ1 (diameter Ͻ 200 nm) predicts very rapid osmotic equilibration times of Ͻ100 ms, even when osmotic water permeability (P f ) is low (Ͻ0.005 cm/s). Other AQPs have been reported in endosomes in some cell types, including AQP6 in the renal proximal tubule and collecting duct epithelial cells (5) and various AQPs in liver cells (6), although data are lacking on their possible cellular functions. Two recent studies reported AQP expression in mitochondria and suggested possible involvement of mitochondrial AQPs in many functions, including metabolism and apoptosis, and in the pathogenesis of neurological diseases such as Parkinson disease.…”
Section: Functionally Significant Expression Of Aquaporin (Aqp)mentioning
confidence: 99%